Resin-adhesive formulations for bonding exterior-type plywood using chilean radiata pine and four hardwoods (1994)
Phenol-formaldehyde resole resins were formulated similarly to plywood resins used in the United States. Some laboratory resins were repeated in a pilot-plant reactor. Specification characteristics were determined on each resin, including viscosity, gel time, nonvolatile solids, and molecular weight. The resins were formulated and mixed with domestic (Chilean) extenders and fillers in plywood-type mixtures similar to the United States caustic-dispersion mixes. The mixtures contained about 28 percent resin solids, 43 percent total solids and 57 percent water. The mixes were used to bond various plywood constructions under varying conditions using Chilean radiata pine (Monterey pine) and four Chilean hardwoods. The plywood panels were tested by an accelerated-aging test method (two 4-h boil test regimen). The results of Ihe tests indicated that the materials and methods were satisfactory for manufacturing exterior-grade plywood according to international Standards including the United States Product Standard PS 1-83.